Peranan Lembaga Bantuan Hukum dalam Penanganan Permasalahan Ketenagakerjaan (Studi Di LBH Bali) - Kresensia Angelica Hardi; Anak Agung Sagung Laksmi Dewi; I Made Minggu Widyantara (Warmadewa Press, 2022)
This study aims to analyze legal aid procedures and determine the role of Legal Aid Institutions in handling employment problems. Legal Aid Institute is one of the distributors of Legal Aid. One of them is the Bali Legal Aid Institute. The scope of the provision of legal aid is quite broad which includes also employment issues considering that many workers' rights have not been fulfilled and the workers' inability to get access to justice. This study uses empirical research methods with a sociological approach. Where researchers make direct observations on objects. Legal aid, procedures, procedures for obtaining legal assistance, and if a problem occurs, its handling is also regulated in Indonesian law. The Bali Legal Aid Institute has an important role in handling labor problems in the Bali area. Its roles include providing legal education, providing assistance, and being involved in policy formation for workers in the Bali area. For the government, it is hoped that it will be more aggressive in providing industrial relations development and for Legal Aid Institutions to socialize Legal Aid so that it can be utilized as well as possible.